Upaya Kepala Madrasah dalam Membimbing Siswa Saat Menggunakan Handphone di Madrasah Ibtidaiyah - Pratiwi, Nensinta Diana; Azis, Abd. (Sekolah Tinggi Agama Islam Pati, 2023)
This research aims to determine the efforts of madrasa heads in guiding students when using cellphones and what are the inhibiting and supporting factors regarding the efforts of madrasa heads in guiding students when using cellphones at Madrasah Ibtidaiyah Miftahul Ulum Gembong for the 2022/2023 academic year. The practical benefit of this research is that it can provide input in efforts to guide students when using cellphones at Madrasah Ibtidaiyah Miftahul Ulum Gembong and the results of this research can be used as input in developing the curriculum. As for the theoretical benefits, it can enrich the literature, especially regarding the use of cellphones. This type of research is field research, with a qualitative approach. Data collection uses interview and documentation techniques. The collected data was analyzed using descriptive analysis. This research will search for and describe the completeness of symptoms, events and cases or activities that are closely related to the efforts of the madrasah head in guiding students when using cellphones at Madrasah Ibtidaiyah Miftahul Ulum Gembong for the 2022/2023 academic year. The results of this research show that: First, the madrasah head's efforts in guiding students when using cellphones in the madrasah are by giving advice to students and drawing closer attention to the students. Second, inhibiting and supporting factors regarding the madrasa head's efforts to guide students when using cellphones at MI Miftahul Ulum Gembong for the 2022/2023 academic year. At this point there are internal and external factors. The inhibiting factors in this research are internal factors external factors. Internal factors include: a) The existence of online learning which makes it more difficult for teachers to guide students when using cellphones; b) Lack of follow-up from students. External factors include a lack of parental attention to students. Supporting factors in this research include internal factors external factors. Internal facts include: a) Active teacher control over students; b) There is a response from students when being advised by the teacher. Meanwhile, external factors are support from parents to the school.